2016
DOI: 10.2139/ssrn.2758688
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Relationship between Investments in Brand Equity and Firm Profitability: Evidence Using Trademark Registrations

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 28 publications
3
23
0
1
Order By: Relevance
“…For the mean cooperative in the regression sample, the percentage translates to $130,441 in net sales. The positive impact in general corresponds to findings in the prior literature (e.g., Agostini et al, ; Crass et al, ; Greenhalgh & Rogers, ). Specifically, the finding is most comparable with Mehrazeen et al () and Agostini et al (), who reported estimates of approximately 0.07% and 0.02%, respectively, on net sales.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…For the mean cooperative in the regression sample, the percentage translates to $130,441 in net sales. The positive impact in general corresponds to findings in the prior literature (e.g., Agostini et al, ; Crass et al, ; Greenhalgh & Rogers, ). Specifically, the finding is most comparable with Mehrazeen et al () and Agostini et al (), who reported estimates of approximately 0.07% and 0.02%, respectively, on net sales.…”
Section: Resultssupporting
confidence: 88%
“…Without consideration of recent additions, variability in net sales is still explained significantly by trademark and service mark ownership. The rising magnitude may even suggest the impact of older trademarks is greater as compared with newer trademarks, which would correspond to the findings of Agostini et al () and Crass et al (). Again, there is not enough time series information to explore if there exists an exponential or an ∩‐shaped relationship.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations